THE IMPORTANCE OF INFORMATION COMMUNICATIONS IN THE FORMATION AND DEVELOPMENT OF COMPETENCE IN STUDENT-YOUTH - Khusinova Laylo Nazarboy qizi (Journals Park Publishing, 2022)
In this article, we will talk about the self-development of the pedagogue in educational activities and the improvement of students' language competence. In doing so, we will also consider the approaches of the pedagogue in the system of improving language skills.
Keywords: Competencies, self-development, pedagogical process, educational material, practice, student